Renewable support, intermittency and market power: An equilibrium investment approach - Ali Darudi; Hannes Weigt (University of Basel, Center of Business and Economics (WWZ), 2019)
Renewable energy sources (RES) play an increasing role in many electricity systems thanks to climate and support policies and subsequent cost reductions in recent years. Compared to conventional generation technologies, RES has two main important distinctive features: First, their cost pattern is characterized by high investment and negligible variable costs and second, their operational decision is governed by weather conditions limiting their availability. In this paper, we aim to analyze the role of RES in electricity markets focusing on the interplay of investment and dispatch decisions under different levels of market competitiveness and different support schemes; namely, feed-in tariff, feed-in premium, and investment subsidies. To this end, we develop a two-stage model of endogenous investment and operation with both intermittent and conventional technologies to obtain analytical solutions for investment and operation decisions. We show that there are feedback effects between the investments of different firms, and between the different technologies of the same firm. Exercise of market power results in underinvestment in the conventional technology; but the effect on renewables is ambiguous due to the interplay of opposing investment incentives. The results furthermore highlight that for the optimal design of a support policy the underlying competiveness of the market needs to be considered.
Keywords: L94; C72; C73; L13; Q42; 330; renewable energy; electricity market; investment; renewable support; market power; two-stage game